Gastrointestinal Parasitic Infections and Immunological Status of HIV/AIDS Coinfected Individuals in Nigeria - Emmanuel Ochigbo Udeh (Ubiquity Press, 2019)
Background: Parasitic infections of the gastrointestinal tract is one of the highest causes of morbidity and mortality among HIV infected individuals. This is due to the colonization of the intestinal tract by parasites influenced by induced enteropathy caused by HIV infection. CD+4 t-lymphocytes count is a marker of the immune status of HIV infected individuals. Objective: This study investigated the prevalence of gastrointestinal parasitic infections among HIV coinfected individuals in relation to their immunological status. Methods: CD+4 t-lymphocytes count was determined using fluorescence-activated cell sorting (FACS) count system. Parasitological examination of faecal samples was conducted using direct wet mount, modified Z-N and Giemsa stain techniques. All prepared slides were examined under x10 and x40 objectives. Findings: Out of the 891 HIV seropositive participants on antiretroviral therapy that were studied, 641 (71.9%) had CD+4 counts equals to or greater than 500 cells/mm3. All other seropositive participants had CD+4 counts below 500 cells/mm3. Gastrointestinal parasitic infections were recorded in 187 (20.9%) seropositive participants, with females (n = 108, 12.1%) having more infections than males. Multiple gastrointestinal parasitic infections were recorded in 28 (3.1%) seropositive participants. Out of the 150 seronegative participants, 79 (52.7%) of them had at least one gastrointestinal parasitic infection. Female seronegative participants also accounted for higher infection rate (n = 42, 28.0%) than males (n = 37, 24.7%). Multiple infections were also recorded in 18 (12.0%) seronegative individuals. The overall prevalence rate of infection between both positive and negative individuals was 25.5%. There was statistical significant difference in the infections of 'Cryptosporidium parvum' (p < 0.003), 'Cyclospora cayetanensis' (p < 0.011) and 'Cystoisospora belli' (p < 0.011) between HIV seropositive and HIV seronegative individuals. Also, there was statistical significant difference in the infections of hook worm (p < 0.002) and 'Trichuris trichiura' (p < 0.020) between seronegative and seropositive individuals. Gastrointestinal parasitic infection rate was significantly higher among seropositive participants with CD+4 counts between 200 and 350 cells/mm3 (n = 109, 58.3%). Conclusion: The study shows that HIV infected individuals continue to experience gastrointestinal infections even with antiretroviral treatment, especially those with CD+4 counts below 350 cells/mm3. Health care providers should prioritise routine screening of HIV patients for gastrointestinal parasites and provide prompt treatment. Antiparasitic drugs should also be provided as prophylaxis.